2011
DOI: 10.1021/ol2016687
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Timing and Tailoring of Macrolactamization in Syringolin Biosynthesis

Abstract: The enzymatic activation of 3,4-dehydrolysine and subsequent formation of the twelve-membered syringolin macrolactam were investigated. The timing of the desaturation was elucidated through the analysis of the initial adenylation domain of SylD. The SylD-TTE didomain was characterized and demonstrated to be the catalyst for formation of twelve-membered macrocycles. When the SylD thioesterase domain was reacted with a family of acyclic CoA both natural and unnatural macrocycles were generated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Sequence and architecture of these genes implied a SylA biosynthesis model also experimentally supported in most of its aspects [54][55][56][57][58] (Figure 2B). Importantly, the structure of SylA with its 12-membered macrolactam ring containing the functional α,β-unsaturated carbonyl group is reflected in the unique architecture of the sylD gene.…”
Section: Occurrence Of Syla Synthetase Genes In P Syringae Strainsmentioning
confidence: 77%
See 1 more Smart Citation
“…Sequence and architecture of these genes implied a SylA biosynthesis model also experimentally supported in most of its aspects [54][55][56][57][58] (Figure 2B). Importantly, the structure of SylA with its 12-membered macrolactam ring containing the functional α,β-unsaturated carbonyl group is reflected in the unique architecture of the sylD gene.…”
Section: Occurrence Of Syla Synthetase Genes In P Syringae Strainsmentioning
confidence: 77%
“…The second SylD NRPS module is thought to activate valine, which, after condensation/decarboxylation to a malonate residue activated by the type I PKS module of SylD, results in a β-keto-thioester whose β-keto group is twofold reduced by the KR and DH domains, thus resulting in the 5-methyl-4-amino-2-hexenoic acid (MAH) moiety. Finally, lactam bond formation between the terminal carboxyl group and the ε-amino group of the 3,4-dehydrolysine moiety catalyzed by the TE domain of the PKS module leads to cyclization and release of the final product [58].…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of the HPLC profiles showed that AP16 produced significantly less syringolin B, C, and E relative to syringolin A than was observed in P. syringae B301D-R (Table 2). In syringolin B, the 3,4-dehydrolysine moiety in the ring structure is replaced by lysine, which, according to the biosynthesis model, results from incomplete lysine desaturation by the sylB gene product, most likely before incorporation (13,17). Thus, lysine desaturation seems considerably more efficient in strain AP16 than in P. syringae B301D-R.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to P. syringae B301D-R, AP16 produces approximately 7-fold less syringolin B and only vanishing amounts of syringolin E in relation to syringolin A. SylB, which is homologous to dihydrorhizobitoxin desaturase (42), is thought to be responsible for the desaturation of lysine to 3,4-dehydrolysine (13). This reaction probably occurs before incorporation into the peptide structure by the first NRPS module of SylD, because its activation domain adenylates 3,4-dehydrolysine much more quickly and more efficiently than lysine (17). The low abundance of syringolin B and E in AP16 shows that lysine is incorporated into the peptide at a much lower rate than in P. syringae B301D-R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation